2009
DOI: 10.1002/elps.200800806
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of glycolytic enzymes in proteins secreted from human colon cancer cells with 5‐fluorouracil resistance

Abstract: 5-Fluorouracil (5-FU) is the most commonly used chemotherapeutic agent for colorectal cancer (CRC). However, resistance to this drug is a major obstacle in CRC chemotherapy. Accurate prediction of response to 5-FU would avoid unnecessary chemotherapy and allow the selection of other effective drugs. To identify a candidate predictor of 5-FU resistance, we isolated secreted proteins that were up- or downregulated in a 5-FU-resistant cancer cell line, compared with the parent cell line (SNU-C4), using a stable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 31 publications
3
57
1
Order By: Relevance
“…This could have clinical implications for the treatment of metastatic colorectal cancer, as it is usually the highly invasive metastatic cancers that are most resistant to conventional chemotherapy, and which may be most sensitive to PDK inhibition. In support of this, a recent study reported that the colorectal tumours resistant to 5-fluorouracil are more likely to have upregulated glycolysis, and hence more amenable to therapy targeting cancer metabolism (Shin et al, 2009). In this regard, our results contrast the findings of Wong et al (2008), who found highly invasive endometrial cancer cells to be most resistant to DCA treatment.…”
Section: Hb2supporting
confidence: 59%
“…This could have clinical implications for the treatment of metastatic colorectal cancer, as it is usually the highly invasive metastatic cancers that are most resistant to conventional chemotherapy, and which may be most sensitive to PDK inhibition. In support of this, a recent study reported that the colorectal tumours resistant to 5-fluorouracil are more likely to have upregulated glycolysis, and hence more amenable to therapy targeting cancer metabolism (Shin et al, 2009). In this regard, our results contrast the findings of Wong et al (2008), who found highly invasive endometrial cancer cells to be most resistant to DCA treatment.…”
Section: Hb2supporting
confidence: 59%
“…Alterations in the activity of human TKT have been reported to cause and/or accompany different pathological disorders, including the Wernicke-Korsakoff syndrome, Alzheimer disease, or diabetes (14 -16). Furthermore, TKT was suggested to be a critical determinant for impaired hippocampal neurogenesis, lymphatic metastasis of hepatocarcinoma, fibromyalgia, tumor cell growth, resistance of colon cancer toward 5-fluoruracil, and female fertility (17)(18)(19)(20)(21).…”
Section: Reactions 1 Andmentioning
confidence: 99%
“…Given the challenges associated with the direct examination of blood fluids there have been attempts to model cancer and other cells in culture byexamining the secreted proteins, where the media represents the circulating blood. However, many of the proteins observed may result from the rapid growth and secretion, but also death and release, of proteins to the culture (Sardana, Marshall, & Diamandis, 2007;Chenau et al, 2009;Shin et al, 2009), and has resulted in the discovery of clusterin as a serological marker of cancer (Gunawardana et al, 2009). A review of the literature shows that many results have been obtained by a wide spectrum of biologists, biochemists, geneticists and analytical scientists thereby demonstrating that protein and peptide MS technologies have advanced to the point that they no longer strictly require specialized knowledge of MS to utilize.…”
Section: A Importance Of Studying Blood Proteins and Peptides By Masmentioning
confidence: 99%